Pengaruh Model Problem Based Learning Terhadap Keterampilan Pemecahan Masalah Fisika Pada Materi Cahaya Dan Alat Optik - Maria Grasia Mbewu (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2024)
The purpose of this study was to determine the significant effect of the problem-based learning model on students' problem solving skills on light and optical devices. This research design uses One-Group Pretest-Posttest Design. The sample used in this study was taken with purporsive sampling technique, namely class VIIIA students of SMP Negeri 9 Kupang, totaling 29 people. The instrument used in this study was a problem-solving skills test question in the form of a description. The data analysis technique in this research is descriptive analysis to describe problem solving skills and statistical tests using paired t test to test the hypothesis. The results showed that the Problem Based Learning (PBL) model had an effect on students' problem solving skills on light material and optical devices. This is seen from the results of the descriptive test of the average percentage of problem solving skills indicators in the pretest of 28% in the very low category and the average posttest percentage of 69% in the moderate category. The results of statistical testing that the significant value of 0.00 is smaller than 0.05 so that Ha is accepted and Ho is rejected which indicates that there is an effect of the PBL model on students' problem solving skills in light and optical devices.